Development of a method for sampling and determination of corrosion inhibitors in modified atmospheres - Silva, Letcia Caetano da [UNESP]; Pereira, Elisabete Alves; Cardoso, Arnaldo Alves [UNESP] (Elsevier B.V., 2015)
A simple and rapid analytical method was developed to determine concentrations of amines used as volatile corrosion inhibitors (VCIs) in protective atmospheres. A microdroplet (16.9 mu L) of an absorbent solution (ethanol/water) was used to collect vapor phase VCIs. Simultaneous separation and determination of the amines was performed using capillary electrophoresis (CE), with indirect detection at a wavelength of 214 nm. The technique was used to measure monoethanolamine (MEA), monocyclohexylamine (MCHA), and dicyclohexylamine (DCHA). It was possible to detect amine in a standard atmosphere after a short time (10 min, including extraction and quantification), while best results were obtained for a total analysis time of 30 min. The method was used to analyze the composition of commercial materials used as VCIs, and revealed that DCHA was the main compound present, with the quantity of inhibitor contained in the plastic support being considerably greater than the amount in the vapor phase. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Volatile corrosion inhibitors (VCIs); Amines; Protective atmosphere; Capillary electrophoresis; Suspended droplet